2020
DOI: 10.1002/admi.201901858
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Poly(para‐xylylene)s—Opportunities and Challenges as Coating Material

Abstract: The chemical vapor deposition (CVD) of poly(para‐xylylene)s (PPX) is an enabling technology for materials design as well as for numerous high‐performance applications. Additionally, PPX possesses of a unique set of structure–property relationships that can be tuned over a wide range. Different strategies vary from functionalization of the most used precursor [2.2]paracyclophane to the testing of new precursors and the copolymerization with various monomers. In this review, some recent developments on synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 99 publications
0
18
0
2
Order By: Relevance
“…Because of the stable low pressure plasma process and no molecular collisions present, the polymer can achieve more similar content of each monomer moiety resulting in better thermal stability which is further analyzed and compared to the classical VDP of poly(p-xylylene). Here, the activation step has been realized in situ by plasma, whereas previous studies showed ( Moss and Greiner, 2020 ) that additional groups such as esters or UV post-treatment can be introduced in order to enable this enhanced linkage and thus stability.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the stable low pressure plasma process and no molecular collisions present, the polymer can achieve more similar content of each monomer moiety resulting in better thermal stability which is further analyzed and compared to the classical VDP of poly(p-xylylene). Here, the activation step has been realized in situ by plasma, whereas previous studies showed ( Moss and Greiner, 2020 ) that additional groups such as esters or UV post-treatment can be introduced in order to enable this enhanced linkage and thus stability.…”
Section: Resultsmentioning
confidence: 99%
“…The CVD process does not require any catalyst, initiator or solvent. The reactive species from chemical precursors are preformed in the vapor phase and spontaneously polymerize without any side products or decomposition of the monomers . The chemical inertness, high purity, flexibility, mechanical strength, and stability of parylenes offer enormous potential in surface modification, optoelectronics, and drug delivery systems and have demonstrated technological utility for coatings of industrial products (e.g., clinically used biomaterials and biomedical devices). Integrating the CVD polymerization process with a template-driven approach can significantly advance capabilities for molecularly controlled structuring of parylenes with tailored shapes, sizes, and chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…Parylene C has received considerable research attention because of its biocompatibility, chemical inertness, and low moisture permeability, which result in it having suitable barrier properties [24][25][26][27][28]. This material has been used in implantable medical devices, such as implantable nerve recording electrodes [29,30], implantable biomedical chips [31,32], drug delivery systems [32,33], spinal cord stimulators [34,35], and cardiac rhythm devices.…”
Section: Introductionmentioning
confidence: 99%